RANCANGAN PROTOTIPE SISTEM DOKUMENTASI KEBIDANAN (CMNOTES) ASUHAN PERSALINAN BERBASIS WEBSITE DI PRODI KEBIDANAN LANGSA - Cut Mutiah; Emilda AS; henni wati; Abdurrahman Abdurrahman (JURNAL KESEHATAN INDRA HUSADA, 2021)
Background: Case Midwifery Notes (CMNotes) is a digital-based documentation system designed to develop learning methods and interactive consultations between students and lecturers as well as clinical instructors. CMNotes facilitates digital and comprehensive recording of patient data starting from assessment, diagnosis, plan of care, implementation to evaluation by applying Varney's management principles and SOAP documentation. Research Objectives: Identifying needs and Designing a Prototype Case Midwifery Notes (CMNotes) documentation system website-based Research Place: Langsa Midwifery Diploma-III Study Program, Aceh, Indonesia Research Design: Research And Development (R&D) to design a website-based prototype of Case Midwifery Notes (CMNotes) documentation system of Maternity Care. Population and Sample: The samples in this study is a total population of 45 respondents. Data collection techniques in this study were interviews and filling out questionnaires. Descriptive data analysis and presented in narrative form Results: The results of the interviews showed that all respondents wanted a digital-based midwifery care documentation application system that could replace the paper-based documentation method. The features available in CMNotes cover all aspects of a standardized midwifery format. The interface in the application is made to be user-friendly and attractive and able to store data properly. There needs to be further development of time efficiency, and features that can analyze important data in the history of pregnancy and childbirth. Kesimpulan : Prototipe CMNotes telah mencakup semua aspek dalam format standar kebidanan dan dapat memudahkan pengguna untuk mendokumentasikan asuhan kebidanan secara digital. Perlu dikembangkan sistem di CMNotes untuk menghitung Interpreted Delivery Date (TTP) dan Usia Kehamilan. Kata kunci: Sistem Dokumentasi, Perawatan Bersalin, Prototipe, Website, CMNotes